Advanced research in the field of transformational leadership - Jörg Felfe; Kathrin Tartler; Detlev Liepmann (Zeitschrift für Personalforschung (ZfP), 2004)
The model of transformational leadership, proposed by Bass (1985), has been widely used in the United States in applied research as well as in practice for more than twenty years. In Germany, as well, this approach has received increasing attention since the late nineties. This article aims to offer a rough introduction to the model proposed by Bass and to provide a general survey on recent German research dealing with this paradigm. First of all, the transferability of the concept to Germany will be discussed. Similarities with results obtained in America are shown and differences thoroughly conferred. Although some limitations and restrictions have to be considered, it can be shown that the concept of transformational leadership is a fruitful approach for leadership research in Germany. Moreover, interesting implications for managerial practice are derived. Furthermore, advanced research questions concerning antecedences and consequences of transformational leadership in Germany are examined. Furthermore, recent findings show that the self-rater version of the MLQ provides additional information concerning the quality of leadership. A detailed look is taken at the relation between leadership and different facets of commitment. It could be shown that there are significant contributions of transformational leadership to affective and normative commitment. Interesting differences appear, if one considers the different contexts. Another direction of current research focuses on the role of followers for the perception and maintenance of transformational leadership. Results indicate that followers' characteristics, such as personality traits and implicit leadership theories, influence the perception and acceptance of transformational leadership.
Keywords: 650; Transformational Leadership; Commitment; Self-/Other Rating; Personality; Multifactor Leadership Questionnaire (MLQ)